Opening Doors: Teaching LGBTQ-themed Young Adult Literature for an Inclusive Curriculum. Issue 1 (2nd January 2018) - Batchelor, Katherine E.; Ramos, Maria; Neiswander, Samantha
ABSTRACT: LGBTQ themes are often neglected in many schools' curriculum. Currently, an LGBTQ-inclusive curriculum framework is not required in most school districts across the county. Therefore, it is important to understand how teachers regard LGBTQ issues; how they address the needs of students in the middle school and high school English classroom who identify on this spectrum or who come from LGBTQ families; and how they incorporate literature that may be considered "controversial" in their future school districts. In this study, English/Language Arts preservice teachers (PSTs) (certification 7–12) were invited to participate in a book club and self-select young adult (YA) literature centering on characters who identify on the LGBTQ spectrum. During two book club meetings, three themes emerged that embody how literature can become a mirror as well as a window for students and assist youth in identity formation and confirmation. Moreover, literature has the potential to empower readers to take action on controversial issues, especially when readers are in positions to make change (no matter how subtle). Although the data collected were from PSTs, our aim with this article is to expand these three themes as overarching messages for practicing educators today, urging the importance of a more inclusive curricula involving LGBTQ literature.